2005
DOI: 10.1139/f05-124
|View full text |Cite
|
Sign up to set email alerts
|

Empirical study of cyanobacterial toxicity along a trophic gradient of lakes

Abstract: A series of 22 lakes in southern Quebec spanning a wide trophic range were sampled to develop models of changes in cyanobacterial abundance and toxicity. All lakes contained toxic cyanobacteria, and epilimnetic toxin content, expressed as microcystin equivalents, was best predicted by total nitrogen concentration and total phosphorus concentration (TP). Although phytoplankton biomass increased linearly with increases in TP among lakes, toxigenic biomass increased as greater than the squared power of TP. The on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 53 publications
10
54
0
2
Order By: Relevance
“…responded positively to increasing phosphorus levels between 0.1 and 0.4 mg phosphorus L -1 and Hee-Mock et al (2000) who showed that phosphorus was an important factor in the control of both the production of microcystin and the type of microcystin produced and that the reduction of phosphorus in eutrophic waters may lower the growth and microcystin producing rate of M. aeruginosa, resulting in reduction of toxic bloom formation. In a recent study of 22 lakes in southern Quebec, Canada, Giani et al (2005) observed stronger responses of toxin concentration to nitrogen content than to TP, which is in concurent to the results of this study.…”
Section: Toxicitysupporting
confidence: 92%
“…responded positively to increasing phosphorus levels between 0.1 and 0.4 mg phosphorus L -1 and Hee-Mock et al (2000) who showed that phosphorus was an important factor in the control of both the production of microcystin and the type of microcystin produced and that the reduction of phosphorus in eutrophic waters may lower the growth and microcystin producing rate of M. aeruginosa, resulting in reduction of toxic bloom formation. In a recent study of 22 lakes in southern Quebec, Canada, Giani et al (2005) observed stronger responses of toxin concentration to nitrogen content than to TP, which is in concurent to the results of this study.…”
Section: Toxicitysupporting
confidence: 92%
“…In contrast to western Canada, MC research in central or eastern Canada is either limited or in its infancy. Giani et al (2005) were identified in blooms collected from Hamilton Harbour, including MCRR, MCYR and MCLR (Murphy et al 2003). Concentrations as high as 400 µg/L were measured at the peak of the blooms.…”
Section: Geographic Distribution Of Microcystinmentioning
confidence: 99%
“…Cylindrospermopsis raciborskii blooms reported in Marola Lake are another evidence of its eutrophic condition, once cyanobacteria blooms generally occur parallel to nutrient enrichment (Watson et al 1997). Due to the water quality deterioration resulting from cyanobacteria growth, freshwater researchers and managers are trying to identify their major causes (Giani et al 2005;Wagner & Adrian 2009) and this became part of our goal in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Other common response to eutrophication is the change in the community structure by the selection of certain morphological or physiological types (Vinebrooke et al 2004). The result is often the dominance of species or groups favored by these modified environmental conditions, such as mixotrophic flagellates and cyanobacteria (Watson et al 1997;Giani et al 2005;Soares et al 2013). Cyanobacteria, or blue-green algae, can be especially dangerous due to their potential toxicity to humans and animals (Carmichael et al 2001).…”
Section: Introductionmentioning
confidence: 99%